Professional self-concept of nurses： the influence of work stressors and related factors - Chen Ji; Luo Ziling; Sun Yue; Ma Lin; Li Ji; Li Xiufang; Deng Xiaorong (Sichuan jingshen weisheng)
BackgroundThe professional self-concept of nurses is a crucial indicator for their personal growth， development and career planning. Previous studies have shown that work stressors during the internship period may lead to a decrease in the level of professional self-concept among nursing students. Given the existing differences in social roles between nursing students and clinical nurses， the influencing factors of professional self-concept in clinical nurses and its relationship with work stressors require further research.ObjectiveTo explore the relationship between work stressors and professional self-concept among nurses， so as to provide references for improving the level of professional self-concept of clinical nurses.MethodsFrom December 2022 to February 2023， a stratified random sampling method was employed to select 260 in-service nurses from Mianyang Hospital of Traditional Chinese Medicine as the study subjects. Chinese Nurses Stressor Scale （CNSS） and Professional Self-concept of Nurses Instrument （PSCNI） were used for assessment. Pearson correlation analysis was conducted to examine the correlation between CNSS scores and PSCNI scores of nurses. Multiple linear regression analysis was utilized to explore the factors influencing the professional self-concept of nurses.ResultsA total of 238 nurses （91.54%） completed valid questionnaires. PSCNI total score yielded a statistical difference among nurses with different marital statuses （F=8.947， P<0.05）. PSCNI total scores were significantly higher in nurses with emergency medical service experience than those without such experience （t=2.208， P<0.05）， and were significantly lower in nurses with abnormal physical examination findings in the past year than those without abnormal findings （t=-2.584， P<0.05）. Correlation analysis revealed that CNSS total score and subscale scores were negatively correlated with PSCNI total score （r=-0.275~-0.169， P<0.01）. Multiple linear regression analysis indicated that work expectation-related stressors， marital status and emergency medical service experience might be influencing factors of their professional self-concept （β=-0.350， 0.345， 0.183， P<0.01）.ConclusionNurses' work stressors are closely correlated with their professional self-concept， and high levels of stressors related to nurses' expectations may lead to a decrease in their professional self-concept levels. ［Funded by 2021 Research Project of Mianyang Municipal Health Commission （number， 202154）］